Subcapsular hepatic pseudocyst as a rare complication of ventriculoperitoneal shunt: A case report - Huda Turkstani; Nouf Albalawi; Amani Azizalrahman; Ali Al-Ameer; Yara AlGoraini (Elsevier, 2022)
Background: Abdominal pseudocysts are an uncommon complication of ventriculoperitoneal shunt (VPS) placement. Patients may be asymptomatic, or present with symptoms such as abdominal pain, abdominal distension, fever, or vomiting. Case presentation: A 13-year-old girl presented to the emergency department complaining of abdominal pain for one week, with a history of VPS insertion for treatment of hydrocephalus in infancy. Diagnosis of an abdominal pseudocyst was made based on abdominal imaging, demonstrating a hepatic cerebrospinal fluid (CSF) pseudocyst free from infection. The patient was managed with aspiration of the CSF pseudocyst, and no intervention was performed on the VPS as the collection was near the distal catheter of the VPS, there were no signs of high intracranial pressure, and the VPS was in a good position. Conclusion: Hepatic pseudocyst is a rare complication of VPS, and can be challenging to diagnose as the primary symptom, acute abdominal pain, is non-specific. Hepatic pseudocyst should be considered when evaluating patients with VPS presenting with abdominal pain.